Cluster spin-glass-like dynamics in Mn-rich La2Ni0.5Mn1.5O6 ferromagnetic insulator. (7th May 2021) - Nasir, Mohammad; Kumar, Sunil; Bera, Anup Kumar; Khan, Mahmud; Yusuf, S M; Sen, Somaditya
Abstract: We report on the physical properties of Mn-rich, nonstoichiometric La2 Ni0.5 Mn1.5 O6 ferromagnetic insulator, prepared by sol-gel method. The single-phase orthorhombic Pbnm structure for the compound was confirmed by x-ray diffraction measurements. Dc magnetization measurements revealed a high saturation magnetization of ∼5.95 μ B /f.u. at 5 K, and a ferromagnetic to paramagnetic transition at ∼162 K. Ac magnetic susceptibility measurements confirmed a broad frequency-dependent anomaly at lower temperatures indicating the presence of spin-glass type magnetic interactions. The ac susceptibility data have been discussed within the framework of the critical slowing down model and Vogel–Fulcher law, and confirmed the cluster spin-glass dynamics with a relaxation time of the order of 10 −5 s. The valence of Ni and Mn ions was verified from the x-ray absorption near edge structure spectroscopy. The origin of cluster spin-glass state was discussed in terms of several possible magnetic exchange interaction pathways among Ni and Mn ions.